The clinical utility of the addition of 64-slice multidetector computed tomography in the investigation of patients with suspected coronary artery disease: initial 2½ year single-centre district general experience. (22nd September 2015) - Asrress, KN; Baldock-Apps, G; Bajpai, A; Giles, JA; Walker, DM; McWilliams, ET
Abstract : Introduction: There are limited data comparing direct coronary angiography (DCA), stress myocardial perfusion imaging (MPI) and 64-slice multidetector cardiac computed tomography (MDCT) in the investigation of patients with suspected coronary artery disease (CAD). When data exist, these have been limited to large tertiary centre series. We set out to analyse retrospectively the impact of introducing MDCT in the work-up of patients presenting to a rapid access chest pain clinic (RACPC), to gain insight into the most appropriate way of utilising it in our diagnostic algorithm. Methods: Clinical details of patients seen in the RACPC between January 2006 and June 2008 were retrospectively reviewed. Patients were assessed by a cardiologist before undergoing non-invasive testing with electrocardiography, transthoracic echocardiography, exercise treadmill testing and biomarkers as necessary. This formed the basis for stratifying patients into a low, intermediate or high risk of significant CAD. Patients were referred to DCA, MPI or MDCT based on these findings. The results were reviewed and conclusions drawn as to the clinical utility of the initial non-invasive imaging versus DCA. Results: 1318 consecutive patients were assessed in the RACPC. The fig summarises their progress. 509 (39%) were felt to be at very low risk of having CAD and were discharged. 809 (61%) required further investigation (mean age 63.4 ± 11.3 years, males 47%). Of these, 32% were at high risk of CAD, 43% were intermediate and a further 25% were low risk, but requiring further investigation. All the high-risk patients were referred for DCA and of 232 subsequently studied 74% had CAD, defined as greater than 50% stenosis in a significant vessel. Patients at low/intermediate risk underwent either MPI, MDCT or DCA. 217 had MPI, of which 72% were negative; 15% were positive and 13% were equivocal—both these groups underwent subsequent angiography, with 48% of those with a positive MPI having CAD and 26% with an equivocal MPI having CAD. MDCT was performed in 107 patients with 86% being negative. Of the patients with a positive MDCT, 11 underwent angiography, of which 64% had significant CAD, with the other 36% having non-obstructive coronary disease. Conclusions: The results show a high number of patients undergoing invasive testing who do not have CAD, and this is most marked in the intermediate/low-risk group. There is an acceptable yield of DCA in patients at high risk of CAD, but in intermediate/low-risk patients almost half of the patients were found to have no significant CAD. A positive stress MPI performed similarly with an over 50% false positive rate. 86% of intermediate/low-risk patients undergoing MDCT had no or minimal evidence of coronary calcification and therefore did not require invasive testing. Our series suggests that the majority of patients deemed at intermediate or low risk of CAD could initially be triaged with MDCT to avoid unnecessary invasive testing with the associated risks and resource implications.